GLOBALISATION: COLONISATION PERPETUATION: A Critique of the Marginalised - Kalliath, Antony (Journal of Dharma, 1999)
At the genesis of Third Millennium, developing nations of Asia, Africa and North America are finding themselves in an inevitable 'critical' situation of two opposing cultural and historical processes: viz. globalisation and subaltern movements. globalisation can be seen as a cultural, political and economic New-Order supported by the Western neo-Iiberal capitalistic ideology envisioned in the logistics of market economy. The present commercial exigencies compel the developing countries to go for globalisation. For example, India's New Economic Policy (NEP) of 1991 is an example .of the tendency towards globalisation. This policy was the result of the World Bank - IMF dictated Structural Adjustment programme. The process of globalisation is accelerated in India with the completion of the Uruguay Round of GATT and the establishment of the World Trade Organisation.